2004
DOI: 10.1021/ja045561v
|View full text |Cite
|
Sign up to set email alerts
|

Full Quantitative Multiple-Scattering Analysis of X-ray Absorption Spectra:  Application to Potassium Hexacyanoferrat(II) and -(III) Complexes

Abstract: A recently developed method to the full quantitative analysis of the XAS spectra extending from the absorption edge to the high-energy region is presented. This method is based on the use of two independent approaches to the analysis of the EXAFS and XANES data, the well-known GNXAS and the newly developed MXAN procedures. Herein, we report the application of this technique to two iron complexes of known structure where multiple-scattering effects are prominent, the potassium hexacyanoferrat(II) and -(III) cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
71
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 17 publications
22
71
1
Order By: Relevance
“…In case of the second sample, where HA S was added in the ratio of 1:10 to the water solution of ferricyanide, we found again six carbon atoms in the first Fe coordination shell at a distance of 1.95 ± 0.01Å with σ 2 = 0.005 ± 0.001Å 2 , and six nitrogen atoms at a distance of 3.14 ± 0.04Å with σ 2 = 0.003 ± 0.001Å 2 . The best-fit values were obtained in both cases with the EXAFS amplitude reduction factor (S 2 0 = 0.95 ± 0.06) and the E o shift (1.0 ± 0.5 eV) which is, within the experimental errors, in agreement with previous findings (Hayakawa et al 2004 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In case of the second sample, where HA S was added in the ratio of 1:10 to the water solution of ferricyanide, we found again six carbon atoms in the first Fe coordination shell at a distance of 1.95 ± 0.01Å with σ 2 = 0.005 ± 0.001Å 2 , and six nitrogen atoms at a distance of 3.14 ± 0.04Å with σ 2 = 0.003 ± 0.001Å 2 . The best-fit values were obtained in both cases with the EXAFS amplitude reduction factor (S 2 0 = 0.95 ± 0.06) and the E o shift (1.0 ± 0.5 eV) which is, within the experimental errors, in agreement with previous findings (Hayakawa et al 2004 ).…”
Section: Resultssupporting
confidence: 91%
“…The structural parameters of the ferricyanide complex before and after the addition of HA S are unchanged, and fully agree with previously reported values for ferricyanide complex in water (Hayakawa et al 2004). The Fe K-edge EXAFS results therefore clearly showed that there are no structural modifications of the ferricyanide complex induced by the interaction with HA S .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This can also be seen from the numerous reported experimental investigations of hexacyanoferrates in the past. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] According to the literature hexacyanoferrate(II) ions, [Fe(CN) 6 ] 4− , are octahedral coordination complexes, which, depending on pH and cyanide concentration, tend to dissociate upon heat or light exposure 14,15,19,31 or in presence of mercury(II), 28 silver(I), 24,28 palladium(II) 28 and gold(III) 28 as they form even stronger complexes with cyanide than iron(II) and iron(III). A degradation of hexacyanoferrates by microorganisms has also been reported.…”
Section: Introductionmentioning
confidence: 99%